(3CbQGW GdPgH aj GdeaGNQI Hjf GdQhVI hHjf GdYQHs - (3YHO Gddg Hf Ydj Hf CMeO Hf eMeO GdMSfj Gdjefj GdUfYGfj, GdeYQha HGdhRjQ,J (B1147 (3g` s ((3jhSa Hf CMeO Hf jhSa Hf GdMSfjf Hf GdMSf s)
(3ChdgG (B:s
(3GdMeO ddg GdPi CfTC LfGJ eYQhTGJ hZjQ eYQhTGJ , HMSH eTJgi YHGOg , hGdfNd hGdRQY eNJdakG Ccdg s
(3BNQgG (B:s
(3hUd jG QH Ydi SGei GdOQM hBdg eG EHJgLJ Jdc GdaQM HeG Qhi HQbhb YfgG haQM hYLd Gddge efc HGdaQM hHGdbHhd cf dfG ebGHdG s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B2s
(3HgG fXGe GdJYbjHIs
(3cJHJ GdYfGhjf HGdMeQIs
(3hgj ebGeI COHjI ai GdefGXQI Hjf GdQhVI hHFQ GdYRH hgeG ef VhGMi UfYGA s
(3JHUQGJ GdCUd (B:s
(3GdfSNI HgG EWGQGJ , RNGQa s
(3eUOQ GbJfGA GdCUd (B:s
Keywords: (3GdLZQGajG h GdHdOGfs